Electrochemiluminescence Study of Europium (III) Complex with Coumarin3-Carboxylic Acid. (13th October 2008) - Lis, Stefan; Staninski, Krzysztof; Grzyb, Tomasz
Abstract : The europium (III) complex of coumarin-3-carboxylic acid (C3CA) has been prepared and characterized on the basis of elemental analysis, IR, and emission (photoluminescence and electrochemiluminescence) spectroscopy. The synthesised complex having a formula Eu( C 3 CA ) 2 ( NO 3 ) ( H 2 O ) 2 was photophysically characterized in solution and in the solid state. Electrochemiluminescence, ECL, of the system containing the Eu(III)/C3CA complex was studied using an oxide-covered aluminium electrode. The goal of these studies was to show the possibility of the use of electrochemical excitation of the Eu(III) ion in aqueous solution for emission generation. The generated ECL emission was very weak, and therefore its measurements and spectral analysis were carried out with the use of cut-off filters method. The studies proved a predominate role of the ligand-to-metal energy transfer (LMET) in the generated ECL.